Decidual cast in patients with endometritis after cesarean: A report of two cases - Kousar Deldar; Seyede Houra Mousavi Vahed; Samira Yaghoubi (Mashhad University of Medical Sciences, 2018)
Introduction: Puerperium infections are the most common types of infection in the post-partum period. Endometritis is 10-20 times more common after cesarean section than vaginal delivery. Symptoms such as fever, vaginal discharge, and abdominal pain are common, but signs and symptoms like vaginal discharge associated with uterine decidual cast and its protrusion into the vaginal canal are rare that can be misdiagnosed as intestinal tissue and omentum. In this article, we report two cases of endometritis following cesarean section with unusual manifestations including mass in the uterine cavity and mass protrusion from the vaginal area due to puerpurial endometritis and decidual casts. Case report: In this article, we report two cases of puerperium infection with uncommon signs including uterine mass and mass protrusion from the cervix with vaginal discharge. In the first case, because of delayed diagnosis and treatment, the patient underwent abdominal hysterectomy due to uterine rupture and omentum protrusion. However, in the second case, because of correct diagnosis and extensive antibiotic therapy and curettage, the uterus was preserved. Conclusion: After vaginal delivery or cesarean section, patients with signs and symptoms of endometritis should undergo antibiotic therapy. In case endometritis persists, sonography should be performed, and if mass in the uterine cavity is observed, curettage should be used. This is because correct and appropriate diagnosis and treatment prevent disease progression and emergency conditions like sepsis, and on rare occasions, vaginal mass protrusion, and thereby, invasive procedures. In addition, in cases of mass in the uterine cavity or mass protrusion from the vaginal area after vaginal delivery or cesarean section, decidual cast should be considered as a differential diagnosis.